System of games for familiarization with chess, in schoolchildren of primary education first cycle - Rolando Díaz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
In these modern times, where the demands are ever greater and the advances in science and technology progress at a dizzying rate, emphasis needs to be placed on efforts towards an ever more developing education. Therefore, priority must be given to learning, to the development of skills, physical abilities, human values and personal resources, in a general sense, in terms of the comprehensive development of the personality. An interview, a survey and observation of the playing time of schoolchildren in the first cycle were carried out and it was found that students prefer the teaching of chess through games. The objective was to propose a system of games to familiarize students with chess in the first cycle, which has been structured based on reality and objectivity, based on the most current precepts on the subject in question. After the application, the results were favorable in terms of the teaching of chess.